Object theater & the indian context (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
The article reflects on the practices with object theater of the Indian Company Tram Arts Trust, their learning and the search to find their artistic identity. Thus, the text dialogues with the creative processes and knowledge arising from these practices.
Keywords: object theater; India; creative processes; Tram Arts Trust